Specific gene transfer to neurons, endothelial cells and hematopoietic progenitors with lentiviral vectors - Anliker, Brigitte; Abel, Tobias; Kneissl, Sabrina; Hlavaty, Juraj; Caputi, Antonio; Brynza, Julia; Schneider, Irene C.; Münch, Robert C.; Petznek, Helga; Kontermann, Roland E.; Koehl, Ulrike; Johnston, Ian C. D.; et al. (Nature methods, 2010)
We present a flexible and highly specific targeting method for lentiviral vectors based on single-chain antibodies recognizing cell-surface antigens. We generated lentiviral vectors specific for human CD105+ endothelial cells, human CD133+ hematopoietic progenitors and mouse GluA-expressing neurons. Lentiviral vectors specific for CD105 or for CD20 transduced their target cells as efficiently as VSV-G pseudotyped vectors but discriminated between endothelial cells and lymphocytes in mixed cultures. CD133-targeted vectors transduced CD133+ cultured hematopoietic progenitor cells more efficiently than VSV-G pseudotyped vectors, resulting in stable long-term transduction. Lentiviral vectors targeted to the glutamate receptor subunits GluA2 and GluA4 exhibited more than 94% specificity for neurons in cerebellar cultures and when injected into the adult mouse brain. We observed neuron-specific gene modification upon transfer of the Cre recombinase gene into the hippocampus of reporter mice. This approach allowed targeted gene transfer to many cell types of interest with an unprecedented degree of specificity.
Gesehen am 23.11.2022